Ecosystem Orchestration: Unpacking the Leadership Capabilities of Anchor Organizations in Nascent Entrepreneurial Ecosystems - Harima, Aki; Harima, Jan; Freiling, Jörg (Entrepreneurship Theory and Practice, 2024)
Although prior research emphasizes the essential role of anchor organizations’ leadership in entrepreneurial ecosystem development in the early stages, their strategic functions are undertheorized. This study conducted a single case study with the entrepreneurial ecosystem of Santiago de Chile as a revelatory case by examining how anchor organizations catalyze the early evolution of the entrepreneurial ecosystem from the perspective of the orchestration theory. We developed a framework of ecosystem orchestration to demonstrate how anchor organizations adapt their strategic functions in managing and building various networks and resources to dynamic environments in entrepreneurial ecosystems.